(untitled) (Fiep Bulletin - online, 2012)
The aim of this study was to evaluate the standard high elevation in children with autism and identify procedures to facilitate the efficient acquisition, retention and transfer of skills for stabilizing the variability of motor action. It was a study case in the Extension in Motor Activity Project to children and teenagers with autism (PREMAUT) from the physical education course of Federal University of Alagoas in Maceió. The sample consisted of five children, aged by 5 to 11 years, diagnosed with autism and the minimum stay in PREMAUT for 18 months. The instruments were: documentary analysis, semi-structured motor tests based on postulates of Gallahue and Ozmun (2005). The Training Program for Motor Skill (THM) consisted of two phases (adaptation and experimentation). The pre-test results showed that subjects (B, C and E) did not perform the task of low complexity of the standard high elevation. The Subjects (A) showed mature stage and (D) elementary stage. In the task of medium complexity, the subjects (B and E) failed to accomplish the task, (A), presented elementary stage, (C and D) initial stage. In the task of high complexity subjects (B) did not perform the task (A and C) and had elementary stage, (D) mature stage (E) initial stage. The Training Motor Skills Program (THA) allowed the subjects to adapt and experiment circuit structured and semi-structured with and without variability of stabilizers plans and teaching resources. The post-test identified positive migration for all subjects assessed in the pre-test. It was concluded that children with autism, from the Program THA, demonstrated acquisition, retention and transfer of skill stabilizer, high elevation, when subjected to circuits with structured variability of tasks, plans and teaching resources in the process of skills training stabilizing.